An interactive timeline visualization for patient cohorts in the oncological routine: a use case on multiple myeloma - Dieter, Julia; Ückert, Frank; Ahlbrandt, Janko; Al-Hmad, Janine; Knurr, Alexander (MEDINFO 2019, 2019)
With the growing interdisciplinarity of cancer treatment and increasing amounts of data and patients, it is getting increasingly difficult for physicians to capture a patient's medical history as a basis for adequate treatment and to compare different medical histories of similar patients to each other. Furthermore, in order to tackle the etiological mechanisms of cancer, it is crucial to identify patients exhibiting a different disease course than their corresponding cohort. Several timeline visualizations have already been proposed. However, the functions and design of such visualizations are always use case dependent. We constructed a cohort timeline prototype mock-up for a specific oncological use case involving multiple myeloma, where the chronological monitoring of various parameters is crucial for patient diagnosis and treatment. Our proposed cohort timeline is a synthesis between elements described in the literature and our own approaches regarding function and design. Dieter, Julia; Ahlbrandt, Janko; Knurr, Alexander; Al-Hmad, Janine; Ückert, Frank
Gesehen am 09.03.2020